2021
DOI: 10.32535/jcda.v4i1.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of The Government in Development of Community-Based Tourism on Economic Growth Inclusivity

Abstract: Tourism sectors have great potentials in increasing regional income. The program from the government to increase the number of tourisms is to prioritize tourism development, one of which is tourism on Lombok Island. The purpose of this study is to evaluate the government role in the development of community-based tourism in Lombok, especially the Mandalika Special Economic Zone in Central Lombok Regency. The analysis technique used in this study is to use convinience sampling techniques that are rarely used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Di mana penghasilan yang mereka dapatkan juga cenderung lebih besar dibandingkan dengan pekerjaan mereka sebelumnya. Pedagang asongan secara tidak langsung membantu meningkatkan perekonomian warga sekaligus membuka lapangan kerja baru (Aprilani & Fathurrahman, 2021). Hal ini didukung oleh beberapa temuan-temuan di lapangan yang dilakukan melalui observasi dan wawancara mendalam pada beberapa pedagang asongan.…”
Section: Hasil Dan Pembahasanunclassified
“…Di mana penghasilan yang mereka dapatkan juga cenderung lebih besar dibandingkan dengan pekerjaan mereka sebelumnya. Pedagang asongan secara tidak langsung membantu meningkatkan perekonomian warga sekaligus membuka lapangan kerja baru (Aprilani & Fathurrahman, 2021). Hal ini didukung oleh beberapa temuan-temuan di lapangan yang dilakukan melalui observasi dan wawancara mendalam pada beberapa pedagang asongan.…”
Section: Hasil Dan Pembahasanunclassified
“…The youth actively engaged in the Karang Taruna organization play a pivotal role in elevating community awareness, diligently monitoring and addressing issues related to illegal mining activities, and fervently advocating for increased local participation and empowerment through ecotourism and Community-Based Tourism (CBT) initiatives. As a core strategy, CBT emphasizes local involvement, ensuring the community reaps tangible benefits from tourism activities (Aprilani, Yuliarmi, & Marhaeni, 2021). It is a resounding symbol of resilience and opposition against mining operations, even during persistent conflicts and tensions.…”
Section: Figure 1 Conflict Mapping and Resolution At Sunor Lestari To...mentioning
confidence: 99%
“…The indicators of governance systems-which include policies and regulations (A 121 ), budgets and subsidies (A 122 ), and government efficiency (A 123 )-aim to evaluate the performances and efficiency of island tourism's various governing systems. Aprilani et al [51] found that the role of official government organizations in island tourism is to plan and develop infrastructure, policies, and regulations. Zgit and Ozturen [52] thought that insufficient and ineffective collaboration and policies are the main obstacles of sustainable island tourism in North Cyprus.…”
Section: Sustainable Island Tourism Evaluation Criteriamentioning
confidence: 99%